Enzymatically crosslinked hyaluronic acid microgels as a vehicle for sustained delivery of cationic proteins. (June 2019) - Jooybar, Elaheh; Abdekhodaie, Mohammad J.; Mousavi, Abbas; Zoetebier, Bram; Dijkstra, Pieter J.
Graphical abstract: Highlights: Hyaluronic acid-based microgels were prepared using a water in oil emulsion method. HA-TA microdroplets were crosslinked via a peroxidase-catalyzed reaction. HA-TA microgels provided a suitable platform for encapsulation of cationic proteins. A cationic protein was released in a sustained manner during a period of four weeks. The simple method of HA-TA microgel fabrication makes the protocol easily scalable. Abstract: In this study, a novel biodegradable hyaluronic acid (HA) based microgel were prepared via enzymatic crosslinking of tyramine conjugated HA (HA-TA) in an inverse microemulsion. HA-TA microdroplets were crosslinked within a few seconds in the presence of horseradish peroxidase (HRP) and hydrogen peroxide (H2 O2 ). The high water content of the polymeric network and the inherent negative charge of the HA-TA microgels provided a suitable platform for encapsulation of cationic proteins like lysozyme and TGF-β1 growth factor. The results demonstrated that lysozyme was released, after an initial burst release, in a suitable sustained manner over a period of four weeks. Both diffusion and degradation due to microgel hydrolysis controlled the release rate. In vitro cytotoxicity of microgels using human mesenchymal stem cells revealed microgels nontoxic. This study demonstrates that the developed injectable HA-TA microgels prepared by enzymatic crosslinking are a promising vehicle for delivery of cationic proteins including some important growth factors.